Free Will, Moral Responsibility, and Scientific Epiphenomenalism - Mele, Alfred R. (Frontiers in Psychology, 2018)
This article addresses two influential lines of argument for what might be termed “scientific epiphenomenalism” about conscious intentions – the thesis that neither conscious intentions nor their physical correlates are among the causes of bodily motions – and links this thesis to skepticism about free will and moral responsibility. One line of argument is based on Benjamin Libet’s neuroscientific work on free will. The other is based on a mixed bag of findings presented by social psychologist Daniel Wegner. It is argued that both lines of argument are unsuccessful.